Cultural Safety: Let’s name it! - Bin-Sallik, Maryann (The Australian Journal of Indigenous Education, 2003)
Abstract This paper provides an overview of the Australian Indigenous higher education sector commencing from its development in the early 1970s to the present. It outlines how the first Indigenous higher education support program was developed, the reasons behind the development, and how and why it has been replicated across the Australian higher education sector. The whole process over the past 30 years of formal Indigenous participation within the higher education sector has been a very difficult process, despite the major gains. On reflection, I have come to believe that all the trials and tribulations have revolved around issues of “cultural safety”, but we have never named it as such. I believe that it is time that we formally named it as a genre in its own right within the education sector. We need to extend it from our psyches and put it out there to be developed, discussed, debated and evaluated. This is what is beginning to take place within Indigenous health - so why not Indigenous education?